Infiltrasi Salafi Wahabi pada Buku Teks di Madrasah dan Respons Warga Nahdliyin - Fuad, A. Jauhar (MarÃƒÂ¢ji`: Jurnal Ilmu Keislaman, 2015)
This article reviews the infiltration of Salafi-Wahabiâs teaching to madrasas through textbooks distributed to several areas, including Kediri. The textbook teaches purification of Islam from various local traditions. It also tells readers about struggles to political Islam either through parliament or the preparation of government regulations. Moreover, it invites readers to acts of violence. The presence of this textbook becomes interesting to be viewed from the politics of education perspective, as it becomes media to foster the ideology of religious movements which slowly goes through the learning process. The process has taken places in Islamic Junior High schools (Madrasa Tsanawiya) and Islamic Senior High Schools (Madrasa Aliya), by inserting an ideology of a certain religious movement through Aqeedah-Akhlaq subject. Responding the presence of the textbook, activists of Nahdlatul Ulama (NU) in Kediri have published counter madrasa textbooks. They have also published Student Worksheets (LKS) Rahmatan lil âAlamin which contents try to strengthen the teaching of NU in madrasas.